Next Generation Low Cost Toll Bridge: An Alternate for Existing National Highway Toll Gate - S., Gopikumar; A., Ahmed Rabick; R., Sheela Daniel (International Journal For Research In Mechanical & Civil Engineering, 2018)
Next Generation Low Cost Toll Bridge - An Alternate for Existing National Highway Toll Gate.